Citation Analysis of Ph.D. Theses Submitted to the University of Delhi in Social Sciences During 1995-2008 - Singh, K. P.; Bebi; Garg, K. C. (Journal of Information and Knowledge, 2014)
The study presents an analysis of citation pattern of Ph.D. theses in social sciences awarded by the University of Delhi during 1995-2008. The study identifies how the pattern of submissions has changed during 1995-2008 in different disciplines of social sciences, besides studying distribution of citations by document types, pattern of authorship of cited documents, cited Indian and foreign authors and chronological distribution of citations. The ranked lists of core journals also have been presented. The analysis reveals that 51,889 citations were made to 259 theses in social sciences. The analysis of these citations shows that books are the most preferred source of citations in all disciplines except economics and constitutes about 55.5% of total citations. The authorship pattern reveals that single authored citations constitute about 86 per cent citations. The chronological distribution of citations shows that the period ranging from 1991 to 2000 is the most cited period. The analyses of journals ranking shows that Economic and Political Weekly published from India is the most cited journal.